2017
DOI: 10.5812/ijem.12555
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitude and Practices (KAP) Regarding Chronic Complications of Diabetes among Patients with Type 2 Diabetes

Abstract: BackgroundTo reduce morbidity and mortality, awareness regarding diabetes and its complications is necessary. This study aimed at assessing the level of knowledge, attitude, and practices (KAP) regarding complications of diabetes mellitus among patients with type 2 diabetes in Dhaka, Bangladesh.MethodsA cross-sectional study was carried out recruiting patients with diabetes from the outpatient department of BIRDEM hospital in Dhaka. Overall, 425 patients with diabetes were enrolled in this study. A pretested q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

53
50
16
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(124 citation statements)
references
References 32 publications
53
50
16
5
Order By: Relevance
“…Most (79.9%) of the respondents reported that they could prevent diabetic complications. This finding is in line with the finding of the same study in Bangladesh where the majority of study participants had reported that they could prevent diabetic complications (11), while in other studies it was only 52.7%, 55.6% and 62.3% in Ethiopia, India and Pakistan respectively (13,15,16). In this study, good glycemic control was assumed to prevent diabetic complications by only 16.9% of respondents.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Most (79.9%) of the respondents reported that they could prevent diabetic complications. This finding is in line with the finding of the same study in Bangladesh where the majority of study participants had reported that they could prevent diabetic complications (11), while in other studies it was only 52.7%, 55.6% and 62.3% in Ethiopia, India and Pakistan respectively (13,15,16). In this study, good glycemic control was assumed to prevent diabetic complications by only 16.9% of respondents.…”
Section: Discussionsupporting
confidence: 91%
“…This study showed that over two third (65.5%) of the study participants had a good attitude level while less than half (48.8%) of study participants had a good practice on DM complications. This finding is supported by a study done in Bangladesh which reported that 66.4% of participants had a good attitude but regarding practice only 20.1% were in good practice (11), which is lower than the finding of the present study. The possible justification may be due to socio-economic and cultural differences.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…6 A study conducted by Rahaman et al in Dhaka, Bangladesh revealed that out of total 425 diabetic respondents, 234 (55.1%) were males and 68 (16%), 204 (48%), 150 (35.3%) were taking oral medication, insulin and combined oral medication and insulin as treatment modality for diabetes and 64% got information about complication of diabetes from physician which showed same results with present study. 7 Abu Hassan et al conducted a study of 21 type 2 DM patients at a primary care clinic who had been on insulin for more than a year stated that about 50% of patients with poor control T2 DM had not started insulin therapy on time and the initiation was usually three to five years after failure of oral medicines and there were many factors influencing delayed insulin initiation, one of the main barriers was psychological insulin resistance defined as psychological opposition towards insulin use among patients and healthcare providers. 8 A study conducted by Feng et al to identify the individual and social factors that are associated with positive healthseeking behaviors and regular maintenance of diabetes showed that out of total 510 respondents, 49.2%, 51.8% were male and female respectively and 42.3% were between 60-80 years of age group and 27.9% were educated up to high school and out of total, 42.2% were taking regular treatment for diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Patients' knowledge of disease and therapy options can have a substantial influence on the development of the disease and its treatment [11]. This shows that proper knowledge of a disease is vital for health and survival; it is critical for the entire disease management process [12]. Moreover, patients' attitude towards their disease affects immediate disease status as well as the long-term outcomes, which shows that their attitude is directly linked to their health status and the occurrence of later complications [13].…”
Section: Introductionmentioning
confidence: 99%